Outcome of HIV patients on ART during the war and siege in a tertiary hospital in Northern Ethiopia: a cross-sectional study - Migbnesh Gebremedhin Weledegebriel; Afewerki Tesfahunegn Nigusse; Tekae Gebru; Hansa Haftu; Teklu Gebrehiwet; Niguse Tsegay; Bisrat Tesfay Abera; Eden Kassahun; Atsede Gebrekidan; Berhane Yohannes Hailu; Samuel Kidane; Rishan Tesfay Desta (Scientific Reports)
Abstract The war and siege in Tigray, Ethiopia, have devastated the region’s health system, critically impacting care for people living with HIV. This study aimed to assess the outcomes and factors affecting HIV patients during this crisis. An independent, repeated cross-sectional study was conducted at Ayder Comprehensive Specialized Hospital between October and November 2022. Data from prewar and during the war periods were analyzed using descriptive statistics and logistic regression. Among 440 participants (mean ages: 39 prewar and 41.2 during war), poor outcomes increased significantly during the war (28.6% prewar vs. 54.5% during war, p < 0.001). ART drug availability dropped by 68.8%, while only 10.6% and 30.7% accessed IPT and CPT, respectively. Services like CD4 and viral load determinations were severely disrupted (p < 0.001), with frequent ART switches and more missed appointments. Prewar factors associated with poor outcomes included severe malnutrition (AOR 3.98; 95% CI 1.04–15.22) and viral load > 1000 copies (AOR 6.68; 95% CI 2.91–15.32). During the crisis, significant factors included travel from distant areas (AOR 2.56; 95% CI 1.14–5.74), CD4 count > 200 cells/ml (AOR 0.27; 95% CI 0.08–0.97). The war and siege in Tigray significantly worsened HIV outcomes by disrupting care services and limiting access to essential treatments.